Experimental Studies on Two-Layer Corium Heat Transfer in Light Water Reactor Lower Head in LIVE2D Facility. (1st September 2020) - Gaus-Liu, Xiaoyang; Cron, Thomas; Fluhrer, Beatrix
Abstract: In-vessel melt retention (IVMR) is a promising strategy in severe accident management for light water reactors. This strategy is not only adopted in the VVER 440 or AP600 reactors, but also included in higher-power reactors around 1000 MW(electric), like the AP1000 and Chinese CPR 1000. There is still a large uncertainty of IVMR by external cooling at powers higher than 1000 MW(electric), and especially where a thin metallic layer appears on the top of a heat-generating oxide layer. Less knowledge based on large-scale experiments is available until now of the interactive physical, chemical, and thermohydraulic processes between the oxide layer and the metallic layer. A test series of naturally separated two liquid layers was conducted in the upgraded LIVE2D test facility in Karlsruhe Institute of Technology using a nitrate salt mixture and high-temperature oil as the lower layer and upper layer simulant, respectively. The transparent front wall of the test vessel enables direct observation of global convection patterns of the melts and the response of the crust at the layer interface. The experiment reveals major thermohydraulic characteristics of the metallic layer during the transient and steady states. The intensity of the heat flux focusing effect in dependence of layer thickness can be clearly identified.